Emulsion-Based Encapsulation of Fibrinogen with Calcium Carbonate for Hemorrhage Control - Henry T. Peng; Tristan Bonnici; Yanyu Chen; Christian Kastrup; Andrew Beckett (Journal of Functional Biomaterials)
Hemorrhage, particularly non-compressible torso bleeding, remains the leading cause of preventable death in trauma. Self-propelling hemostats composed of thrombin-calcium carbonate (CaCO3) particles and protonated tranexamic acid (TXA+) have been shown to reduce blood loss and mortality in severe bleeding animal models. To further enhance both hemostatic and self-propelling properties, this study was to investigate fibrinogen-CaCO3 particles prepared via a water-oil-water (W/O/W) emulsion method. The particles were characterized using light and fluorescence microscopy, gel electrophoresis, rotational thromboelastometry (ROTEM), and video motion tracking. The method produced spherical micrometer-sized particles with various yields and fibrinogen content, depending on the preparation conditions. The highest yield was achieved with sodium carbonate (SC), followed by ammonium carbonate (AC) and sodium bicarbonate (SBC). AC and paraffin generated smaller particles compared to SC and heptane, which were used as the carbonate source and oil phase, respectively. Fibrinogen incorporation led to an increase in particle size, indicating a correlation between fibrinogen content and particle size. Fluorescence microscopy confirmed successful fibrinogen encapsulation, with various amounts and hemostatic effects as assessed by gel electrophoresis and ROTEM. Combining fibrinogen-CaCO3 particles with TXA+ and thrombin-CaCO3 particles showed synergistic hemostatic effects. All fibrinogen-encapsulated particles exhibited self-propulsion when mixed with TXA+ and exposed to water, regardless of fibrinogen content. This study advances current hemostatic particle technology by demonstrating enhanced self-propulsion and fibrinogen incorporation via the W/O/W emulsion method. Further optimization of the encapsulation method could enhance the effectiveness of fibrinogen-CaCO3 particles for hemorrhage control.